Chemical analysis of fish bile extracts for monitoring endocrine disrupting chemical exposure in water: Bisphenol A, alkylphenols, and norethindrone. (30th November 2015) - Wu, Minghong; Pan, Chenyuan; Yang, Ming; Xu, Bentuo; Lei, Xiangjie; Ma, Jing; Cai, Ling; Chen, Jingsi
Abstract: The present study determined concentrations of estrogenic bisphenol A (BPA), nonylphenol, octylphenol (4‐tert‐octylphenol), butylphenol (4‐tert‐butylphenol), and progestogenic norethindrone by liquid chromatography–tandem mass spectrometry in bile extracts from field fish from the Xin'an River and market fish in Shanghai, China. Compared with the field fish, endocrine disrupting chemical (EDC) concentrations in market fish bile were at relatively high levels with high detectable rates. The average concentrations of BPA, nonylphenol, 4‐tert‐octylphenol, 4‐tert‐butylphenol, and norethindrone in field fish bile were 30.1 µg/L, 203 µg/L, 4.69 µg/L, 7.84 µg/L, and 0.514 µg/L, respectively; in market fish bile they were 240 µg/L, 528 µg/L, 76.5 µg/L, 12.8 µg/L, and 5.26 µg/L, respectively; and in the surface water of Xin'an River they were 38.8 ng/L, 7.91 ng/L, 1.98 ng/L, 2.66 ng/L, and 0.116 ng/L, respectively. The average of total estrogenic activity of river water was 3.32 ng/L estradiol equivalents. High bioconcentration factors (BCFs) were discovered for all 5 EDCs (≧998‐fold) in field fish bile. Furthermore, the authors analyzed the BCF value of BPA in fish bile after 30‐d exposure to environmentally relevant concentrations of BPA in the laboratory, and the analysis revealed that BCF in fish bile (BCFFish bile ) changed in an inverse concentration–dependent manner based on the log10‐transformed BPA concentration in water. Strikingly, the data from the field study were well fitted within this trend. The data together suggested that analysis of fish bile extracts could be an efficient method for assessing waterborne EDCs exposure for aquatic biota. Environ Toxicol Chem 2016;35:182–190. © 2015 SETAC